Religious Sermons by Nursalim, Hidayat, and Basalamah on YouTube/TikTok: Impacts on Bogor Residents' Tolerance Knowledge and Attitudes - Fakhrudin, Fakhrudin; Wibisono, M. Yusuf; Nase, Nase (Hanifiya: Jurnal Studi Agama-Agama, 2026)
This study examines the impact of Islamic preaching content delivered by K.H. Ahmad Bahauddin Nursalim (Gus Baha), Ustadz Adi Hidayat, and Ustadz Khalid Basalamah via YouTube and TikTok on the religious knowledge and tolerance attitudes of the urban Muslim community in Bogor, Indonesia. Employing a sequential explanatory mixed-methods approach, the research integrates quantitative survey data analyzed via multiple regression with qualitative insights gathered from in-depth interviews with local religious figures and community members. The findings reveal that 88.2% of the variance in religious tolerance behavior is attributable to the consumption of digital religious content on these platforms. While TikTok contributes to the rapid dissemination of visualized religious messages, YouTube offers more structured, in-depth religious discourse, both of which reinforce spiritual awareness and interfaith empathy. The study concludes that social media platforms play a transformative role in shaping urban religiosity, functioning as digital spaces for ethical formation, theological education, and inclusive civic identity. Theoretically, this research contributes to the growing discourse on digital religious literacy, demonstrating how algorithm-driven environments mediate new modes of religious engagement. Practically, it provides actionable insights for religious institutions and policymakers to design adaptive and pluralist religious communication strategies in an increasingly mediated society.